(untitled) (Fiep Bulletin - online, 2013)
The aim of the sports training is the increase and the improvement of the physical performance. Whenever the intensity, duration and the daily working load are not appropriate, positive physiological adaptations occur. However, there is a fairly subtle delimitation between an outstanding performance and a decrease in it due to overtraining. Overtraining may include: lesion and muscular weakness; cytosine activation; hormonal and hematological alterations; mood swings; psychological depression and nutritional problems which may lead to loss appetite and diarrhea. Several studies about overtraining have been conducted with the effort to identify its causes, symptoms, hypotheses, besides the markers that could identify it. Nevertheless, its diagnosis is very difficult since the overtraining symptoms are similar to the ones from preovertraining and to the ones from normal training, making it difficult to dissociate them.